Recent Trends in Medicare Utilization and Reimbursement for Orthopaedic Procedures Performed at Ambulatory Surgery Centers. (4th August 2021) - Lopez, Cesar D.; Boddapati, Venkat; Schweppe, Eric A.; Levine, William N.; Lehman, Ronald A.; Lenke, Lawrence G.
Abstract : Background: As part of a market-driven response to the increasing costs of hospital-based surgical care, an increasing volume of orthopaedic procedures are being performed in ambulatory surgery centers (ASCs). The purpose of the present study was to identify recent trends in orthopaedic ASC procedure volume, utilization, and reimbursements in the Medicare system between 2012 and 2017. Methods: This cross-sectional, national study tracked annual Medicare claims and payments and aggregated data at the county level. Descriptive statistics and multivariate regression models were used to evaluate trends in procedure volume, utilization rates, and reimbursement rates, and to identify demographic predictors of ASC utilization. Results: A total of 1, 914, 905 orthopaedic procedures were performed at ASCs in the Medicare population between 2012 and 2017, with an 8.8% increase in annual procedure volume and a 10.5% increase in average reimbursements per case. ASC orthopaedic procedure utilization, including utilization across all subspecialties, is strongly associated with metropolitan areas compared with rural areas. In addition, orthopaedic procedure utilization, including for sports and hand procedures, was found to be significantly higher in wealthier counties (measured by average household income) and in counties located in the South. Conclusions: This study demonstrated increasing orthopaedic ASC procedure volume in recent years, driven by increases in hand procedure volume. Medicare reimbursements per case have steadily risen and outpaced the rate of inflation over the study period. However, as orthopaedic practice overhead continues to increase, other Medicare expenditures such as hospital payments and operational and implant costs also must be evaluated. These findings may provide a source of information that can be used by orthopaedic surgeons, policy makers, investors, and other stakeholders to make informed decisions regarding the costs and benefits of the use of ASCs for orthopaedic procedures.